Water stresses and responses in Myanmar’s Central Dry Zone - Drury, L.; Johnston, R.; Schmitter, Petra S. (Springer, 2023)
The Central Dry Zone (CDZ) of Myanmar is the heartland of the Burmese culture, and in many ways, it is socially and culturally coherent with the other rice-centred cultures of mainland Southeast Asia. In climatic terms, it is a semi-arid outlier in a mostly wet-tropical region. Climate change is exacerbating weather variability and water insecurity, and the CDZ thus epitomises the challenges posed by climate change for much of the region. This chapter describes two examples of interventions aimed at addressing water insecurity in the CDZ: pumped irrigation at Pyawt Ywar; and artesian groundwater in the Pale Subbasin. Both address the interconnections between social and physical drivers of vulnerability. They demonstrate the challenges and importance of working across institutional scales. These examples demonstrate that progress is possible at local levels despite a lack of (or inappropriate) national policy and regulations, which limit the scale, and possibly the long-term sustainability of such gains.